POTENTIAL OF COGON GRASS AS AN OIL SORBENT - Edi Iswanto Wiloso; Vera Barlianti; Irni Fitria Anggraini; Hendris Hendarsyah (Research Center for Chemistry - LIPI, 2012)
Experiments on the potential of Cogon grass (lmperata cylindrica), a weed harmful to other plants, for use as a low-cost and biodegradable oil sorbent were carried out under various spill conditions. Flowers of Cogon grass adsorbed much larger amount of high-viscosity lubricating oil (57.9 g-oil/g-sorbent) than that adsorbed by Peat Sorb (7.7 g-oil/g-sorbent), a commercial oilsorbent based on peat. However, the flowers adsorbed only 27.9 g of low-viscosity crude oillgsorbent. In an oil-water system, the mount of oil adsorbed was influenced by the level with which the two were mixed: vigorous stirring reduced the sorption capacity by 36%. The high sorptive capacity of the flowers can be attributed to their hydrophobic nature and good oil-wettability. The flowers showed good buoyancy even after 24 hours of shaking under conditions that simulated water ripple (gentle wary motion) in sea, which suggests their potential in combating oil spills both on land and in water.Keywords: Sorbent; Oil spill,' Oil sorption; Cogon grass;Imperata cylindrica